André du Bouchet : poetic forms of attention - Wagstaff, Emma (Collection monographique Rodopi en littérature française contemporaine, 2020)
"In André du Bouchet: Poetic Forms of Attention, Emma Wagstaff provides the first book-length study in English of this major poet of the second half of the twentieth century. She shows how Du Bouchet's rigorous and innovative creative and critical writing advances our understanding of attention. Du Bouchet is known as a post-war poet of the natural world and the space of the page. Far from just a solitary writer, however, he engaged with others through his work as editor, critic, and translator, and his involvement in the protests of May 1968. Emma Wagstaff shows how his writing demonstrates nuanced attention to language, time, nature, and art, and incites a 'slow' response on the part of the reader"--